Prevalence of bacteria isolated from the respiratory tracts infection from clinical specimens of patients in Roi Et Hospital between 2015 to 2017 - Putthanachote, Nuntiput; Munjit, Siriporn; Panta, Nuchnapa; Sangsa, Narongchai; PongKaew, Orathai; phuangsriken, Satchawan; Charoensaen, Jumrusluk; Treesorn, Kumaleeporn; Kucharin, Paphatchaya; Gudwongsa, Wongklang; Sarakran, Pongdech (Archives of Allied Health Sciences, 2019)
Nosocomial infection is seriously public health problem worldwide. The infection patients are complicate to treat and high risk of mortality. The respiratory tracts are the important organs of body that high prevalence of infections. Objective, to study the prevalence of bacteria isolated from the respiratory tracts infection from clinical specimens of patients in Roi Et Hospital between 2015 to 2017. Method, this study was descriptive study. All data were collected from the Division of Clinical Microbiology Laboratory, Roi Et Hospital during January 1, 2015 to December 31, 2017. All data were from clinical specimens of respiratory tract isolation. The descriptive statistical analyses were used. Results, in 2015, the totals were 5,203 isolates. The top five isolations were Acinetobacter baumannii 25.49%, Pseudomonas aeruginosa 19.03%, Klebsiella pneumoniae 12.01%, Klebsiella pneumoniae (ESBL-producing strain) 9.71%, Stenotrophomonas maltophilia 4.02%. In 2016, the totals were 5,488 isolates. The top five isolation were Acinetobacter baumannii 28.37%, Pseudomonas aeruginosa 19.53%, Klebsiella pneumoniae 13.88%, Klebsiella pneumoniae (ESBL-producing strain) 7.94%, Stenotrophomonas maltophilia 4.54%. In 2017, the totals were 5,964 isolates. The top five isolations were Acinetobacter baumannii 27.05%, Klebsiella pneumoniae 20.86 %, Pseudomonas aeruginosa 20.30%, Escherichia coli 5.42%, Stenotrophomonas maltophilia 4.98%. Conclusion, the prevalence of bacteria isolated from respiratory tracts infection in Roi Et Hospital was high. The most commonly pathogens isolated were Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, Stenotrophomonas maltophilia and Escherichia coli.